APPROXIMATED EVALUATION OF A RIGID ACOUSTIC CAVITY COUPLED ON A FLEXIBLE BOARD IN A FREE VIBRATION - Teodoro da Silva, Agnaldo Antonio Moreira; Morais, Marcus Vinícius Girão de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The study of the acoustic behavior of a cavity depends on factors such as acoustic wavelength, cavity dimensions, the effect of flexible interface structures, making it relatively complex problem. Due to the complexity of the problem it’s sought simplified methods for the purpose techniques analysis applied with greater ease. Pretlove and Craggs (1969) presented a two-dimensional analysis of a cavity coupled to a plate using the normal mode as an approximation for explaining experimental results and then compared with results obtained by other authors. Recently Rojas (2015) presented an analytical solution to a rigid acoustic cavity coupled to a flexible plate in free vibration using an approximation by weighted residuals (Galerkin Ritz). The present study performed an analysis adding another modal forms to the Pretlove and Craggs’ works (1969) in order to evaluate the method’s efficiency. The comparisons with the Pretlove’s (1965) semi-analytical results and with the Rojas’ (2015) analytical results are the validation of this present study, checking a good approximation with the results.